2008 IEEE Intelligent Vehicles Symposium 2008
DOI: 10.1109/ivs.2008.4621174
|View full text |Cite
|
Sign up to set email alerts
|

The histogram feature - a resource-efficient Weak Classifier

Abstract: Abstract-This paper presents a Weak Classifier that is extremely fast to compute, yet highly discriminant. This Weak Classifier may be used in, for example, a boosting framework and is the result of a novel way of organizing and evaluating Histograms of Oriented Gradients. The method requires only one access to main memory to evaluate each feature, in comparison with the more well-known Haar features which require somewhere between six and nine memory accesses to evaluate each feature. This low memory bandwidt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 9 publications
0
28
0
Order By: Relevance
“…Pettersson et al [5] showed that a significant bottleneck for such systems is memory bandwidth. It was observed that memory access to the precomputed datatype for Haar features was faster than the memory bandwidth allowed.…”
Section: Balancing Processor and Memory Bandwidthmentioning
confidence: 99%
See 4 more Smart Citations
“…Pettersson et al [5] showed that a significant bottleneck for such systems is memory bandwidth. It was observed that memory access to the precomputed datatype for Haar features was faster than the memory bandwidth allowed.…”
Section: Balancing Processor and Memory Bandwidthmentioning
confidence: 99%
“…Pettersson et al [5], introduced a novel precomputed image which they called the histogram image. The histogram image is used in a similar way to the precomputed images for other features, but has one major advantage in terms of speed.…”
Section: Balancing Processor and Memory Bandwidthmentioning
confidence: 99%
See 3 more Smart Citations